Political forces mobilized about the 2003 referendum in colombia (2008)
The reformations proposed by president Uribe in the referendum affected, in a differential way, the interests of economic associations, unions and political parties and movements in Colombia. The article analyzes alliances and the types of mobilization of political forces to defend their interests, the spread of an electoral option that they considered most convenient (“Yes”, “No”, or abstention) and the pedagogic approaches used by promoters and opponents.